Digitalization of the Awarding Process in Bulgaria During a Pandemic - Pavlova, Miglena (UNWE Yearbook, 2021)
The spread of COVID-19 in the past year has posed a serious challenge to state economies. The pandemic had an impact on the management and economy of developing countries and transition countries, which required the reorganization of management methods and increased use of information and communication technologies in everyday life. This complex and unexpected environment has altered the way the public administration works, which reflects on the business as well. Bulgaria was not isolated from the effect and took measures, including legislative measures to deal with the situation. In parallel with these processes, a serious reform in the “Public Procurement” sector was carried out in Bulgaria related to the digitalization of the awarding process. Digitalization has led to streamlining the process of conducting public procurement procedures and has enabled its effectiveness to be improved.
Keywords: Electronic procurement; Public services; Public procurement; Electronic platform for the award process; Procurement awarding